Cambridge Grammar for First Certificate with Answers: self-study grammar reference and practice - Hashemi L. Louise (Cambridge Books for Cambridge Exams)
Do you want to be confident that you have covered all the grammar for the First Certificate exam? Would you like to improve your listening skills at the same time? Cambridge Grammar for First Certificate provides comprehensive coverage of the grammar needed for the updated exam and gives you the chance to hear grammar being used in different situations, as well as offering plenty of exam practice. Presents grammar in a listening context. Contains clear and reliable grammar explanations with lots of examples. Practises the range of First Certificate exam tasks from the Use of English, Reading, Listening and Writing papers. Encourages analysis of the languageDo you want to be confident that you have covered all the grammar for the First Certificate exam? Would you like to improve your listening skills at the same time? Cambridge Grammar for First Certificate provides comprehensive coverage of the grammar needed for the updated exam and gives you the chance to hear grammar being used in different situations, as well as offering plenty of exam practice. Presents grammar in a listening context. Contains clear and reliable grammar explanations with lots of examples. Practises the range of First Certificate exam tasks from the Use of English, Reading, Listening and Writing papers. Encourages analysis of the language. Includes helpful grammar glossary